Pengaruh Adversity Quotien Terhadap Kemampuan Pemecahan Masalah Matematis Dalam Menyelesaikan Soal Bertipe Hots Berdasarkan Langkah Polya - Dini Dini; Ahmad Yani T; Dian Ahmad; Ade Mirza; Agung Hartoyo (Universitas Hamzanwadi, 2026)
The influence of Adversity Quotient (AQ) on students' mathematical problem-solving in answering Higher Order Thinking Skills (HOTS) type questions based on Polya’s steps is highly essential. This research employed an ex-post facto method involving 60 eleventh-grade students of SMA Bawari Pontianak. Data were collected through the measurement of students’ Adversity Quotient levels and a mathematical problem-solving test designed in accordance with Polya’s four-step process: understanding the problem, devising a plan, carrying out the plan, and reviewing the solution. The analysis results indicated a highly significant effect of Adversity Quotient on students' mathematical problem-solving abilities. A significance value of 0.00 (< 0.05) and a Pearson correlation coefficient of 0.421 suggest a moderately strong positive relationship. Students with high to very high Adversity Quotient tended to solve HOTS-type problems more systematically and effectively compared to those with moderate or low AQ. They were also more capable of completing all four of Polya’s steps comprehensively. These findings highlight that mental resilience, perseverance, and the ability to manage pressure are critical factors in successfully solving high-level mathematical problems. Therefore, strengthening students’ Adversity Quotient through instructional strategies and non-cognitive support is strongly recommended to enhance their problem-solving quality.